2021
DOI: 10.3390/su13041758
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of Purchase Intention at Starbucks in the Context of Covid-19 Pandemic

Abstract: The purpose of this research is to examine the determinants of coffee shop purchase intention. The research domain is Starbucks, which is the brand ranked first in the coffee shop market. This study selects healthiness, hygiene, quarantine, ease of app use, and environmental responsibility as candidates for the antecedents of purchase intention. For hypothesis testing, this research used a survey and recruited survey participants using Amazon Mechanical Turk, and carried out multiple linear regressions to test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
47
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 72 publications
8
47
0
5
Order By: Relevance
“…The perceived ease of use is also relevant to the online shopping experience, strongly associated with the purchase intention (Moslehpour et al 2018). In a study related to the purchase intention of a particular brand of coffee, it was possible to observe that the ease of App (software application) use positively affects the purchase intention in coffee services (Shim et al 2021).…”
Section: Perceived Ease Of Purchasementioning
confidence: 99%
See 1 more Smart Citation
“…The perceived ease of use is also relevant to the online shopping experience, strongly associated with the purchase intention (Moslehpour et al 2018). In a study related to the purchase intention of a particular brand of coffee, it was possible to observe that the ease of App (software application) use positively affects the purchase intention in coffee services (Shim et al 2021).…”
Section: Perceived Ease Of Purchasementioning
confidence: 99%
“…It is imperative to understand the trend and impacts of the COVID-19 pandemic on consumer buying behavior (Addo et al 2020) and how to expand the understanding of the effect of COVID-19 on consumers and consumer crops (Kim 2020). There is a need for more studies on the effect of risk perception toward epidemics on consumer behavior and decision making (Shim et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Further, Konuk (2019) showed that food quality and price fairness are positively associated with revisit intention of an organic food restaurant. Shim et al (2021) also found that hygiene and quarantine have positive impacts on the purchase intention of caf e products. Kim (2017) explored the link between environmental CSR and customer intention, and showed that environmental CSR has a positive effect on purchase intention in the food business sector.…”
Section: Hypotheses Development and Research Modelmentioning
confidence: 89%
“…As COVID-19 is a stumbling block to sales growth in the coffee shop business in Korea, coffee shop operators are trying to minimize losses by focusing on quarantine [6]. Despite this, dozens of employees and customers at the Starbucks' Paju store in South Korea have been infected [7], which shows the importance of contactless service in the food service industry [4].…”
Section: Introductionmentioning
confidence: 99%